Inflammation Investigated as a Source of Pharmacokinetic Variability of Atazanavir in AIDS Clinical Trials Group Protocol A5224s. Issue 4 (May 2018) - Venuto, Charles S; Lim, Jihoon; Messing, Susan; Hunt, Peter W; McComsey, Grace A; Morse, Gene D
Background: Inflammation is associated with the down-regulation of drug metabolizing enzymes and transporters. Thus, we investigated the chronic inflammatory state associated with HIV infection as a source of pharmacokinetic variability of atazanavir. We also explored the association of total bilirubin concentrations with markers of inflammation and endothelial activation. Methods: Apparent oral clearance (CL/F) of atazanavir was estimated from plasma samples collected from participants in AIDS Clinical Trials Group Study A5202. Several inflammatory and endothelial activation biomarkers were measured at baseline and weeks 24 and 96 as part of metabolic substudy A5224s: high-sensitivity C-reactive protein (hsCRP), interleukin-6, tumour necrosis factor-α and its soluble receptors, soluble vascular cellular and intracellular adhesion molecules and total bilirubin. Statistical analysis was performed by a matrix of correlation coefficients between atazanavir CL/F and biomarker concentrations measured at week 24. The correlation between atazanavir clearance and percentage change in bilirubin from baseline to weeks 24 and 96, and between biomarkers and bilirubin concentrations at each week were also evaluated. Results: Among 107 participants, there were no significant correlations observed between atazanavir CL/F and inflammatory and endothelial activation bio-markers measured at week 24 ( P ≥0.24). As expected, bilirubin increased with increasing exposure to atazanavir (rho=-0.25, P =0.01). Bilirubin concentrations were inversely correlated ( P <0.01) with each of the biomarkers except hsCRP. Conclusions: Atazanavir CL/F did not correlate with the inflammatory biomarkers changes. Inflammatory-mediated inhibition of cytochrome P450 3A may have been attenuated due to atazanavir-associated increases of bilirubin, which has known anti-inflammatory properties.